Assessing the relationship between near-infrared spectroscopy-derived regional cerebral oxygenation and neurological dysfunction in critically ill adults: a prospective observational multicentre protocol, on behalf of the Canadian Critical Care Trials Group. Issue 6 (25th June 2019) - Wood, Michael D; Khan, Jasmine; Lee, Kevin F H; Maslove, David M; Muscedere, John; Hunt, Miranda; Scott, Stephen H; Day, Andrew; Jacobson, Jill A; Ball, Ian; Slessarev, Marat; O'Regan, Niamh; et al.
Abstract : Introduction: Survivors of critical illness frequently exhibit acute and chronic neurological complications. The underlying aetiology of this dysfunction remains unknown but may be associated with cerebral ischaemia. This study will use near-infrared spectroscopy to non-invasively quantify regional cerebral oxygenation (rSO2 ) to assess the association between poor rSO2 during the first 72 hours of critical illness with delirium severity, as well as long-term sensorimotor and cognitive impairment among intensive care unit (ICU) survivors. Further, the physiological determinants of rSO2 will be examined. Methods and analysis: This multicentre prospective observational study will consider adult patients (≥18 years old) eligible for enrolment if within 24 hours of ICU admission, they require mechanical ventilation and/or vasopressor support. For 72 hours, rSO2 will be continuously recorded, while vital signs (eg, heart rate) and peripheral oxygenation saturation will be concurrently captured with data monitoring software. Arterial and central venous gases will be sampled every 12 hours for the 72 hours recording period and will include: pH, PaO2, PaCO2, and haemoglobin concentration. Participants will be screened daily for delirium with the confusion assessment method (CAM)-ICU, whereas the brief-CAM will be used on the ward. At 3 and 12 months post-ICU discharge, neurological function will be assessed with the Repeatable Battery for the Assessment of Neuropsychological Status and KINARM sensorimotor and cognitive robot-based behavioural tasks. Ethics and dissemination: The study protocol has been approved in Ontario by a central research ethics board (Clinical Trials Ontario); non-Ontario sites will obtain local ethics approval. The study will be conducted under the guidance of the Canadian Critical Care Trials Group (CCCTG) and the results of this study will be presented at national meetings of the CCCTG for internal peer review. Results will also be presented at national/international scientific conferences. On completion, the study findings will be submitted for publication in peer-reviewed journals. Trial registration number: NCT03141619